Improved pharmacokinetics of tenofovir ester prodrugs strengthened the inhibition of HBV replication and the rebalance of hepatocellular metabolism in preclinical models - Hong, Xiaodan; Cai, Zuhuan; Zhou, Fang; Jin, Xiaoliang; Wang, Guangji; Ouyang, Bingchen; Zhang, Jingwei (Frontiers in Pharmacology, 2022)
Tenofovir (TFV) ester prodrugs, a class of nucleotide analogs (NAs), are the first-line clinical anti-hepatitis B virus (HBV) drugs with potent antiviral efficacy, low resistance rate and high safety. In this work, three marketed TFV ester drugs, tenofovir disoproxil fumarate (TDF), tenofovir alafenamide fumarate (TAF) and tenofovir amibufenamide fumarate (TMF), were used as probes to investigate the relationships among prodrug structures, pharmacokinetic characteristics, metabolic activations pharmacological responses and to reveal the key factors of TFV ester prodrug design. The results indicated that TMF and TAF exhibited significantly stronger inhibition of HBV DNA replication than did TDF in HBV-positive HepG2.2.15 cells. The anti-HBV activity of TMF was slightly stronger than TAF after 9 days of treatment (EC50 7.29±0.71 nM vs. 12.17±0.56 nM). Similar results were observed in the HBV decline period post drug administration to the HBV transgenic mouse model, although these three TFV prodrugs finally achieved the same anti-HBV effect after 42 days treatments. Furthermore, TFV ester prodrugs showed a correcting effect on disordered host hepatic biochemical metabolism, including TCA cycle, glycolysis, pentose phosphate pathway, purine/pyrimidine metabolism, amino acid metabolism, ketone body metabolism and phospholipid metabolism. The callback effects of the three TFV ester prodrugs were ranked as TMF>TAF>TDF. These advantages of TMF were believed to be attributed to its greater bioavailability in preclinical animals (SD rats, C57BL/6 mice and beagle dogs) and better target loading, especially in terms of the higher hepatic level of the pharmacologically active metabolite TFV-DP, which was tightly related to anti-HBV efficacy. Further analysis indicated that stability in intestinal fluid determined the actual amount of TFV prodrug at the absorption site, and hepatic/intestinal stability determined the maintenance amount of prodrug in circulation, both of which influenced the oral bioavailability of TFV prodrugs. In conclusion, our research revealed that improved pharmacokinetics of TFV ester prodrugs (especially intestinal stability) strengthened the inhibition of HBV replication and the rebalance of hepatocellular metabolism, which provides new insights and a basis for the design, modification and evaluation of new TFV prodrugs in the future.